2021
DOI: 10.1051/e3sconf/202132801012
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Fermented Leek (Allium porrum L.) Cultured by Lactobacillus plantarum B1765 to Deliver Probiotics

Abstract: This study aims to detect the food safety of blood coockle satay sold by street vendors in Surabaya Indonesia, in terms of bacterial contamination and Cadmium heavy metal content. This research is a descriptive research with survey method. The sampling technique was carried out randomly from 15 street vendors, for further testing of bacterial contamination which included total bacteria, Coliform bacteria, and detection of heavy metal Cadmium (Cd) in blood coockle satay. The results showed that of all (15) sata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…Propionic acid is the highest SCFA grew in this study, reaching 2.01±0.0004 mg/mL at 36 hours of fermentation from an initial concentration of 0.84±0.0258 mg/mL. This result is supported by the research [20][21], which showed that the fermentation of yacon and garlic as inulin sources with Lactobacillus plantarum B1765 resulted in the highest propionic acid content among other SCFA types. This is due to propionic acid having three formation pathways: the acrylate, succinate, and propanediol pathways.…”
Section: The Effect Of Fermentation Time On the Production Of Short C...supporting
confidence: 77%
See 1 more Smart Citation
“…Propionic acid is the highest SCFA grew in this study, reaching 2.01±0.0004 mg/mL at 36 hours of fermentation from an initial concentration of 0.84±0.0258 mg/mL. This result is supported by the research [20][21], which showed that the fermentation of yacon and garlic as inulin sources with Lactobacillus plantarum B1765 resulted in the highest propionic acid content among other SCFA types. This is due to propionic acid having three formation pathways: the acrylate, succinate, and propanediol pathways.…”
Section: The Effect Of Fermentation Time On the Production Of Short C...supporting
confidence: 77%
“…L. plantarum B1765 can also act as a probiotic characterized by its ability to withstand the pH of the gastrointestinal tract and is antagonistic to pathogenic bacteria [19]. In addition, L. plantarum B1765 has been known to form SCFA using inulin from yacon [20] and inulin from single garlic [21].…”
Section: Introductionmentioning
confidence: 99%